Effect of cryopreservation on the viability and the biocontrol activity of Nomuraea rileyi against Spodoptera frugiperda (Lepidoptera: Noctuidae) - TORRES, LISSETTE; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2005)
The entomopathogenic fungus Nomuraea rileyi is one of the most promising alternatives for the control of Spodoptera frugiperda, the most important pest of maize in Colombia. In previous work, a native isolate of N. rileyi was selected that caused 100% mortality on larvae of the pest under laboratory conditions. However, biocontrol activity of microorganisms may be affected by different factors such as preservation method. This study determined the effect of cryopreservation in glycerol and peptone at - 70°C on its viability and biocontrol activity over time. From a suspension of 1 x 107 conidia.ml-1, germination percentage, number of colony-forming units (CFU) and percent efficacy of the microorganism on larvae were determined before cryopreservation (control), after 24 hours, 12 months and 18 months. An effect on the viability of the microorganism expressed as percent germination and as CFU was not evident 24 hours after cryopreservation with respect to the control; but after 12 months there was a delay of 18 hours to reach a percent germination above 90% and a one exponent loss to CFU. However, no significant differences were detected in moth mortality in any of the evaluated times, being higher than 96.4%. It is concluded that cryopreservation over 18 months does not affect the germination or the biocontrol activity but does affect the CFU.